The Relationship Between Psychological Skills and Achievement Levels Among Students in All Three Stages of the Faculty of Physical Education and Sports Sciences in Handball - Kadhim Mhmood Abed AL-Delfi (Psikologia : Jurnal Psikologi, 2027)
General Background: Athletic performance depends on physical, technical, tactical, and psychological preparation, particularly in sports requiring rapid responses under competitive pressure. Specific Background: Handball students encounter changing situations that require concentration, emotional control, confidence, anxiety management, mental imagery, and achievement motivation. Knowledge Gap: Previous research had not specifically examined the relationship between psychological preparation and performance outcomes among students from different academic levels within the selected college context. Aims: This study evaluates psychological skill levels, examines their relationship with handball performance, and compares students from the first, second, and fourth academic years. Results: A descriptive correlational design involved 75 students, including 15 participants in the pilot study and 60 in the main study. The adopted instrument contained 24 items distributed across visualization, relaxation, concentration, anxiety management, self-confidence, and athletic achievement motivation. Test–retest reliability reached 0.88, while dimension coefficients ranged from 0.85 to 0.87. First-year students recorded the highest reported psychological stress level at 73%, compared with 42% among second-year students and 21% among fourth-year students. The comparison between the first and second years was statistically significant (t = 3.2), whereas comparisons involving the fourth year were reported as nonsignificant. The study concluded that selected psychological capacities improved more than others and were strongly associated with performance outcomes. Novelty: The research presents a stage-based comparison linking six psychological dimensions with practical handball performance. Implications: Academic programs should integrate structured mental preparation to strengthen confidence, concentration, emotional regulation, and competitive readiness. Highlights: First-year participants recorded the highest reported stress level at 73%. Second- and fourth-year cohorts presented lower values of 42% and 21%. Mental preparation was reported as strongly associated with practical performance outcomes. Keywords: Psychological Skills, Achievement Sports Sciences, Handball.